PENGARUH KEPEMIMPINAN KIAI DAN KEPUASAN GAJI TERHADAP KINERJA UMANA’ DI LINGKUNGAN PENDIDIKAN TINGGI PONDOK PESANTREN SALAFIYAH SYAFI’IYAH SUKOREJO SITUBONDO - Nanda Hidayan Sono (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2021)
This study aims to analyze the influence of kiai leadership on umana' performance and the effect of salary satisfaction on umana' performance partially, as well as the influence of kiai leadership and salary satisfaction on umana' performance simultaneously. This type of research uses a field research method (Field Research) with a quantitative approach. The sampling technique in this study used the Simple Random Sampling technique to 51 respondents. This study uses statistical analysis consisting of classical assumption test and multiple linear regression analysis. The results of this study indicate that the kiai's leadership has a partially significant effect on umana' performance with a sig. t = 0.003 < = 0.1. Salary satisfaction has no partial effect on umana' performance with a sig value. t = 0.762 > = 0.1. The kiai's leadership and salary satisfaction have a simultaneous effect on umana' performance with a sig. f = 0.004 < = 0.1.